Natural convection and entropy generation of nanofluid filled cavity having different shaped obstacles under the influence of magnetic field and internal heat generation - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2015)
In this study, natural convection in a nano-fluid filled cavity having different shaped obstacles (circular, square and diamond) installed under the influence of a uniform magnetic field and uniform heat generation was numerically investigated. The cavity was heated from below and cooled from the vertical sides while the top wall was assumed to be adiabatic. The temperatures of the side walls vary linearly. The governing equations were solved by using Galerkin weighted residual finite element formulation. The numerical investigation was performed for a range of parameters: external Rayleigh number (10(4) <= ROE <= 10(6)), internal Rayleigh number (10(4) <= Ra-I <= 10(6)), Hartmann number (0 <= Ha <= 50), and solid volume fraction of the nanofluid (0 <= phi <= 0.05). It is observed that the presence of the obstacles deteriorates the heat transfer process and this is more pronounced with higher values of Re-E. Averaged heat transfer reduces by 21.35%, 32.85% and 34.64% for the cavity with circular, diamond and squared shaped obstacles compared to cavity without obstacles at Ra-I = 10(6). The effect of heat transfer reduction with square and diamond shaped obstacles compared to case without obstacle is less effective with increasing values of Hartmann number. Second law analysis was also performed by using different measures for the normalized total entropy generation. (C) 2015 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: MHD flow; Obstacle; Nanofluids; Heat generation; Finite element method